Fructose metabolism and its role in pig production: A mini-review - Xie, Jiahao; Shi, Shiyi; Liu, Yucheng; Wang, Shaoshuai; Rajput, Shahid Ali; Song, Tongxing (Frontiers in Nutrition, 2022)
Epidemiological studies have shown that excessive intake of fructose is largely responsible for the increasing incidence of non-alcoholic fatty liver, obesity, and diabetes. However, depending on the amount of fructose consumption from diet, the metabolic role of fructose is controversial. Recently, there have been increasing studies reporting that diets low in fructose expand the surface area of the gut and increase nutrient absorption in mouse model, which is widely used in fructose-related studies. However, excessive fructose consumption spills over from the small intestine into the liver for steatosis and increases the risk of colon cancer. Therefore, suitable animal models may be needed to study fructose-induced metabolic changes. Along with its use in global meat production, pig is well-known as a biomedical model with an advantage over murine and other animal models as it has similar nutrition and metabolism to human in anatomical and physiological aspects. Here, we review the characteristics and metabolism of fructose and summarize observations of fructose in pig reproduction, growth, and development as well as acting as a human biomedical model. This review highlights fructose metabolism from the intestine to the blood cycle and presents the critical role of fructose in pig, which could provide new strategies for curbing human metabolic diseases and promoting pig production.